Willingness to pay for domestic water service improvements in Selangor, Malaysia : a choice modeling approach - Yacob, Mohd Rusli; Radam, Alias; Samdin, Zaiton (Canadian Research & Development Center of Sciences and Cultures, 2011)
The tasks and responsibilities of domestic water service management in Malaysia are handled by various government agencies. Sufficient water service and resources management is required for sustainable water resources conservation. In order to realized water resource conservation, economic effectiveness of water utilization (consumers), maintenance of water quality supply (source of water supply) and efficiency in allocating water resources (agencies) needs to be addressed. The objective of the study is to assess community preferences and values relating to alternative water service management with particular concentration on water service improvement. This study has applied Choice Experiment (CE) to investigate the current policies and potential alternative of water service management in Selangor. The studies are based on 230 respondents in Subang Jaya that were randomly interviewed for data collection in October to December 2008. The findings indicates that respondents are willing to pay higher for drinking water as compared to the current rate with improved in water quality (WQ), reduced the frequency of water interruption (WI) and increases in the consumer trust to tap water (CT). The finding of this study is very important in order to assists and recommends the policy makers towards efficiency of domestic water service management in Malaysia.